Sec24C/D-isoform-specific sorting of the preassembled ER-Golgi Q-SNARE complex - Adolf, Frank; Rhiel, Manuel; Reckmann, Ingeborg; Wieland, Felix T. (Molecular biology of the cell, 2016)
Secretory proteins are exported from the endoplasmic reticulum in COPII vesicles. SNARE proteins—core machinery for membrane fusion—are incorporated into COPII vesicles by direct interaction with Sec24. Here we report a novel mechanism for sorting of the ER-Golgi Q-SNAREs into COPII vesicles. Different mammalian Sec24 isoforms recruit either the R-SNARE Sec22b or the Q-SNAREs Syntaxin5, GS27, and Bet1. Syntaxin5 is the only Q-SNARE that directly interacts with Sec24C, requiring its “open” conformation. Mutation within the IxM cargo-binding site of Sec24C led to a drastic reduction in sorting of all three Q-SNAREs into COPII vesicles, implying their ER export as a preassembled complex. Analysis of immunoisolated COPII vesicles and intracellular localization of Sec24 isoforms indicate that all ER-Golgi SNAREs are present on the same vesicle. Combined with existing data, our findings yield a general concept of how Sec24 isoforms can recruit fusogenic SNARE subunits to keep them functionally apart and thus prime mammalian COPII vesicles for homotypic fusion.